Dicer ablation in osteoblasts by Runx2 driven cre-loxP recombination affects bone integrity, but not glucocorticoid-induced suppression of bone formation - Liu, Peng; Baumgart, Mario; Groth, Marco; Wittmann, Jürgen; Jäck, Hans-Martin; Platzer, Matthias; Tuckermann, Jan P.; Baschant, Ulrike (Scientific Reports, 2016)
Glucocorticoid-induced osteoporosis (GIO) is one of the major side effects of long-term glucocorticoid (GC) therapy mediated mainly via the suppression of bone formation and osteoblast differentiation independently of GC receptor (GR) dimerization. Since microRNAs play a critical role in osteoblast differentiation processes, we investigated the role of Dicer dependent microRNAs in the GC-induced suppression of osteoblast differentiation. MicroRNA sequencing of dexamethasone-treated wild-type and GR dimer-deficient mesenchymal stromal cells revealed GC-controlled miRNA expression in a GR dimer-dependent and GR dimer-independent manner. To determine the functional relevance of mature miRNAs in GC-induced osteoblast suppression, mice with an osteoblast-specific deletion of Dicer (Dicer(Runx2Cre)) were exposed to glucocorticoids. In vitro generated Dicer-deficient osteoblasts were treated with dexamethasone and analyzed for proliferation, differentiation and mineralization capacity. In vivo, abrogation of Dicer-dependent miRNA biogenesis in osteoblasts led to growth retardation and impaired bone formation. However, subjecting these mice to GIO showed that bone formation was similar reduced in Dicer(Runx2Cre) mice and littermate control mice upon GC treatment. In line, differentiation of Dicer deficient osteoblasts was suppressed to the same extent as wild type cells by GC treatment. Therefore, Dicer-dependent small RNA biogenesis in osteoblasts plays only a minor role in the pathogenesis of GC-induced inhibition of bone formation.
EVALuna2:13640